Potensi Fungi Rizosfer Tanaman Damar (Agathis dammara) Sebagai Agensia Biokontrol Fusarium oxysporum - Galang Anahatta Hidayat; Arif Rahman Hikam; Yuriza Eshananda; Brenda Liestyaning Adi; Tyas Wanda Septiani (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Plant diseases become one of the dangerous threats to agriculture. Fusarium oxysporum is one of pathogen that attack many agricultural plants. The spread of plant pathogens must be controlled. One of the way to control plant pathogens is to use biological control methods by utilizing biocontrol agents using antagonistic fungi to control F. oxysporum. Antagonistic fungi can be found in various habitats such as rhizosphere soil that contains a lot of exudate released by the roots so that the area is rich in organic compounds. Sampling was carried out in the rhizosphere soil of Damar plants from the Baturraden Botanical Garden. Research on antagonistic fungi from the plant rhizosphere needs further exploration. Therefore, this study was conducted to obtain isolates of rhizosphere fungi that have potential as antagonists against F. oxysporum. This research was carried out with method stages ranging from sampling, isolation, characterization and identification to antagonism tests. The isolation results stated that five different fungi were found from the rhizosphere of the Damar plant. The fungi found were then tested for antagonistic ability against F. oxysporum and it was found that R5 isolate had the best ability to inhibit the growth of F. oxysporum with an inhibitory percentage value of 72.06%. This ability can be new information to be able to develop further about the potential of large plant rhizosphere fungi in their inhibition against plant pathogens.